Antioxidant Activity of Bajakah Kuning (Arcangelisia flava (L.) Merr) - Herman, Herman; Almaida, Maria; Haeruddin, Haeruddin; Bone, Mahfuzun; Rusman, Arman (Journal of Tropical Pharmacy and Chemistry, 2024)
Indonesia is a tropical country with potential plants that have been used as traditional medicine for generations. One of them is bajakah. This study aims to determine the phenolic content and antioxidant activity of yellow bajakah extract and the relationship between phenolic content and antioxidant activity. The study began with making yellow bajakah extract using maceration method. The bajakah extract obtained then analysed the phenolic content quantitatively using the Folin-Ciocalteu method. Antioxidant activity was tested using the DPPH and ABTS methods. The results showed that yellow bajakah extract contained phenolic compounds with levels of 27.15 ± 1.28 mg/g GAE. IC50 measurements to determine antioxidant activity obtained a value of 47.01 ± 1.16 µg / ml in the DPPH method and 61.21 ± 0.83 µg / ml in the ABTS method. Based on these results, yellow bajakah skin is known to have antioxidant activity with a strong category and phenolic content in yellow bajakah skin has an influence on antioxidant activity.